2004
DOI: 10.1002/poc.848
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base behavior of triazoleporphyrazines in proton‐donating media

Abstract: The acid–base properties of some peripheral substituted triazoleporphyrazines in proton‐donating media with poor‐donating character were experimentally studied. The substitution of one pyrrole moiety in the porphyrazine‐like compounds by one triazole ring in the triazoleporphyrazines leads to an increase in the basicity. The protonation of the triazoleporphyrazines results in a hypsochromic shift of the Q‐bands in the UV–visible spectra. A DFT study of some selected structural models of the unsubstituted triaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20] The π-conjugation in molecular systems underwent important factors in all photophysical properties. The idea to prepare molecular photoswitches by controlling π-conjugation using photochromic compounds was first illustrated by Lehn and Irie [21][22][23][24][25] and enhanced by Tian group [26][27][28] to exploit molecular properties and create molecular switches.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] The π-conjugation in molecular systems underwent important factors in all photophysical properties. The idea to prepare molecular photoswitches by controlling π-conjugation using photochromic compounds was first illustrated by Lehn and Irie [21][22][23][24][25] and enhanced by Tian group [26][27][28] to exploit molecular properties and create molecular switches.…”
Section: Introductionmentioning
confidence: 99%
“…Previously it was found that the introduction of two 1,2,4triazole rings to the phthalocyanine molecule, replacing two opposite isoindole rings, resulted in an ABAB-type system with little conjugation in the macroring, 5,6 but replacement of only one isoindole subunit by a triazole ring leads to the formation of an aromatically conjugated macrosystem similar to that of phthalocyanine. Thus, aromatic triazolephthalocyanines [7][8][9] and triazoleporphyrazines [10][11][12] have been synthesised.…”
Section: Introductionmentioning
confidence: 99%